(untitled) (Research, Society and Development, 2021)
The aim of this study is to analyze the perception of internet users about the most accessed recipes in gastronomic media from the perspective of food and nutrition. Quantitative and qualitative study of a clipping of digital media content related to gastronomy and published on the internet, on the YouTube® page. The Panelinha® channel was selected, dedicated to the dissemination of recipes and culinary videos related to food. The comments of two videos with the highest number of views by internet users were transcribed, categorized and interpreted by content analysis. The most viewed posts were “How to make the perfect omelet - creamy, fluffy... hmmm!”, with 1 million hits and “In one pot: Risotto by Rita Lobo with 453 thousand views. The categories raised were: positive feedback, praise to the recipe, praise to the presenter/channel, negative feedback, doubts, suggestions, criticisms. In the video “How to make the perfect omelet” 235 posts were analyzed, 38% made by women and 55% by men and 7% without gender identification. Video with shorter duration, fewer ingredients and greater simplicity in applied techniques, associated with a healthy appeal, reached a greater number of Internet users. The longest video, “In a pot: Rita Lobo’s risotto”, with 91 comments, 71% made by women, 26% by men and 3% without gender identification. Video with a recipe with more ingredients and preparations, aroused greater interest in the female audience, however, raised more doubts. These videos were able to distribute the most positive opinions of users, who acted as encouraging agents for the practice of healthy eating shown.